2016
DOI: 10.1016/j.neuron.2016.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Targeted Optogenetics and Electrical Microstimulation Reveal the Primate Koniocellular Projection to Supra-granular Visual Cortex

Abstract: Electrical microstimulation and more recently optogenetics are widely used to map large-scale brain circuits. However, the neuronal specificity achieved with both methods is not well understood. Here we compare cell-targeted optogenetics and electrical microstimulation in the macaque monkey brain to functionally map the koniocellular lateral geniculate nucleus (LGN) projection to primary visual cortex (V1). Selective activation of the LGN konio neurons with CamK-specific optogenetics caused selective electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 55 publications
3
80
0
1
Order By: Relevance
“…Such specificity is unusual for viral vector-mediated gene delivery in primates. The modest payload of viral vectors and the presumed length of cell type-specific promoters challenge the feasibility of this approach, and several attempts to achieve targeting in this way have yielded only moderate specificity (Delzor et al, 2012; Klein et al, 2016; Kügler, 2015; Nathanson et al, 2009a). However, the present study shows that some types of primate neurons can be targeted with precision using short promoters, complementing recent promising efforts described below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such specificity is unusual for viral vector-mediated gene delivery in primates. The modest payload of viral vectors and the presumed length of cell type-specific promoters challenge the feasibility of this approach, and several attempts to achieve targeting in this way have yielded only moderate specificity (Delzor et al, 2012; Klein et al, 2016; Kügler, 2015; Nathanson et al, 2009a). However, the present study shows that some types of primate neurons can be targeted with precision using short promoters, complementing recent promising efforts described below.…”
Section: Discussionmentioning
confidence: 99%
“…A CaMKIIa promoter (1.3 kb) in an AAV vector was used to activate koniocellular projections from the macaque lateral geniculate nucleus to primary visual cortex, achieving a specificity of 54–88% (Klein et al, 2016). A tyrosine hydroxylase (TH) promoter (3.1 kb) in a lentiviral vector was used to target dopaminergic neurons of macaques, achieving a specificity of 96% (Lerchner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were conducted using average local field potential (LFP) responses across stimulation trials and current source-density (CSD) profiles were calculated for the visual flicker and optogenetic conditions to assess V1 laminar activation. Of the total population of LGN neurons recorded, the authors identified 23% as being directly affected by the optogenetic stimulation, in comparison to the ~10% observed in the literature (Klein et al, 2016). Although less than 50% of the cells were activated, the authors were able to confirm that at the neuronal circuit level, the amount of selectively recruited K-cells was sufficient to drive short-latency activity in the supra-granular layers of downstream area V1 (Klein et al, 2016).…”
Section: Journal Of Young Investigatorsmentioning
confidence: 79%
“…Macaques were used to study visual information processing mechanisms in the lateral geniculate nucleus (LGN) and primary visual cortex (V1) by administering an AAV with an effective CamKII promoter into koniocellular cells (K-cells) at the LGN (Klein et al, 2016). The LGN is made up of K-cells, parvo cells and magno cells, each distinct in their circuitry, function and biochemistry, despite all passing through the V1.…”
Section: Journal Of Young Investigatorsmentioning
confidence: 99%
See 1 more Smart Citation